Analysis of Manpower Planning Based on Digital Economy in Cianjur Regency - Gatiningsih (International Journal of Science and Society, 2021)
There are three main characteristics of labor problems in Indonesia: First, the high growth rate of the workforce due to the rapid flow of population growth entering the working age. Second, the number of the labor force is large, but the average has low education, and third, the labor force participation rate is high, but the average income of workers is low. This research uses qualitative methods with a descriptive analysis approach. The study was conducted in the Cianjur Regency area. Analysis of current and future employment conditions through quantitative descriptive analysis methods assisted by statistical tools. For this reason, the data used in the framework of this study are Susenas data. This research shows that the low quality of the population is a barrier to economic development. This is mainly due to the low level of education and knowledge of the workforce. The economy of Cianjur Regency in 2020 grew by 7.35%, and employment growth by 4.84%, with an elasticity of 0.6585. So that the number of job opportunities in 2015 was 354,201 people. Meanwhile, the economic forecast for Cianjur Regency in 2020 will grow by 7.72% and employment growth by 4.14%, with an employment elasticity of 0.5363. It is estimated that GRDP at the constant price of Cianjur Regency is Rp. 10,012.91 billion, and job opportunities created as many as 438,490 people.